Evliya Çelebi’nin Kosova’daki Seyahati – 1660 (4th International Balkan Studies Congress Proceedings, 2025)
Evliya Çelebi was one of the greatest chroniclers in Ottoman history. His travels to various places worldwide and his descriptions of cities, cultures, and historical events are a primary source of cultural and historical writing from this period. His writings serve as a historical and literary connection, much like other Ottoman chroniclers such as Neshri, Aşık Paşazade, Kemal Paşazade, Tur-sun Bey, etc. Evliya Çelebi’s “Seyahatname” (Book of Travels) includes the cul-tural history, folklore, and geography of the places he visited, one of which is Kosovo. Evliya Çelebi’s journey to Kosovo took place in the mid-17th century, during the reign of Sultan Mehmed IV (1648-1687). During this journey, Evliya Çelebi, accompanied by Melek Ahmet Pasha, visited cities such as Zveçan, Mit-rovica, Vushtrri, Pristina, Kaçanik, and Skopje. While describing these cities, he also recounts the history of the cities and the sultans who ruled these regions. For instance, he describes the Mitrovica Fortress as an unfortunate fortress be-cause it is known as the place where Sultan Murad I was killed. He also mentions the mosques, tombs, inns, and lodges in these cities, as well as the foods more commonly consumed in Kosovo, such as baklava. One of his notable visits was to the tomb of Sultan Murad Hüdavendigâr. Additionally, he explains the etymology of city names, such as how Kaçanik was derived from “Kaçanlar.” The primary source for this topic is Evliya Çelebi’s work “Seyahatname” and his descriptions of his travels. Other significant works examining Evliya Çelebi’s travels include those by authors such as Salih Vuçitërrni, Hasan Kaleshi, Franz Babinger, Jup Kastrati, Ahmet Cevdet, Dankoff, and Robert Elsie. Using a scientific methodo-logy, we will draw specific conclusions about Evliya Çelebi’s historic journey to Kosovo through these sources.